Perbandingan Kinerja Saham Konvensional dan saham syariah di Pasar Modal - Irgi Priantito; Nadia Asandimitra Haryono (Universitas Negeri Surabaya, 2026)
This study aims to identify and explain the comparative performance of conventional and Sharia-compliant stocks in the capital market using the calculating return and standard deviation to measure returns and risks. It is a quantitative descriptive study whose population comprises stocks listed on the Jakarta Islamic Index (JII) and the IDX30 during 2020–2024. Samples were drawn via purposive sampling, selecting companies that met specific criteria to provide relevant data. Statistical analysis was performed using an Independent Samples t-test in SPSS Statistics 25. Quantitative descriptive methods were employed, with stock returns and risks (standard deviation) as performance indicators. Purposive sampling selected 7 Sharia and 7 conventional stocks consistently listed during the period. Statistical analysis using the Independent Samples t-test in SPSS 25 showed no significant differences in returns or risks between Sharia and conventional stocks. External factors such as the COVID-19 pandemic, government policies, and global market fluctuations contributed to this convergence. The results indicate no significant difference in returns or risks between Sharia-compliant and conventional stocks. This lack of distinction is attributed to the economic downturn caused by the COVID-19 pandemic, as well as external factors such as government policies, interest rate movements, currency fluctuations, and global market volatility. These findings imply that Sharia-compliant stocks offer financial performance comparable to conventional stocks, supporting their viability for Muslim investors.